Perceptions Of Computer-Supported Collabprative Learning (Cscl) And Its Effect On Learning Performance, Self-Regulated Learning And Sustainability Behaviors - Charoenwet, Salubsri (2009)

(untitled)
A student social network was established under EU-SUPPORT based on computer-supported collaborative learning (CSCL). The EU-SUPPORT network is a sub network of the Norwegian Environmental Education Network that focuses on schools to promote the quality of education for sustainable development. The investigation into CSCL network involved examining participation and quality of discussion/interaction, the degree of knowledge building in this collaborative network and the effect of learning environment on learning performance, self-regulated learning behaviors, sustainability behaviors as well as students’ perception of the CSCL environment. Participants were 200 secondary school students from Malaysia and Thailand.